Utilization of Home Telemonitoring in Patients 75 Years of Age and Over with Complex Heart Failure. (January 2013) - Lemay, Geneviève; Azad, Nahid; Struthers, Christine
We conducted a chart review on all patients who had received home telemonitoring after an admission for heart failure at the University of Ottawa Heart Institute. During a 5 year period (2005–2009) a total of 645 patients had home monitoring. A total of 594 patients met the inclusion criteria for the study and were divided into two groups: Group 1 (<75 years of age) contained 350 patients and Group 2 (≥75 years of age) contained 244 patients. There was no significant difference between the groups in the mean duration of follow-up by the telemonitoring team: it was 126.5 days in Group 1 and 125.4 days in Group 2 ( P = 0.89). There were no significant differences between the groups in the number of times that titration of diuretic medications occurred, the number of times that titration of cardiac medications occurred, the number of interventions for abnormal vital signs or the number of times that patients were called by the telemonitoring staff. Emergency room visits, hospitalizations and the number of deaths were also not different between two groups. Thus in the telemonitoring programme, the pattern of usage by older patients was similar to that of the younger ones. Based on the present study, the elderly do not require more resources nor do they require them for longer.